Sources of phosphorus for beef cattle - Richardson, D.; Smith, E.F.; Koch, B.A.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
In a previous test it was found that phosphoric acid can be used as a source of phosphorus for beef heifer calves on dry bluestem pasture. A phosphorus balance study with lambs also indicated efficient use of phosphorus from phosphoric acid. This test was conducted to further evaluate phosphoric acid as a source of phosphorus in the wintering and fattening ration under dry-lot feeding conditions.
Keywords: Beef; Phosphorus; Feed efficiency; Phosphoric acid